1999
DOI: 10.1001/archpsyc.56.8.741
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral Deficits at Adolescence in Children at Risk for Schizophrenia

Abstract: Results are consistent with the hypothesis that individuals at genetic risk for schizophrenia may display lifelong neurobehavioral signs that are indicators of vulnerability to schizophrenia and that are associated with psychiatric adjustment generally and schizophrenic spectrum disorder specifically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
81
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 84 publications
7
81
1
1
Order By: Relevance
“…Abuse and neglect are known to have a negative influence on cognitive functioning in community samples of healthy adults 20,21 and children/adolescents 22,23 as well as in patients with psychosis. 8,24,25 Congruent with other studies, [26][27][28] we have reported that children from densely affected multigenerational families who had a parent affected by schizophrenia or BD had fullscale IQ impairments as well as deficits in specific cognitive domains, such as visual and verbal episodic memory, working memory and executive functions of initiation. 12,16 These domains are among the most impaired in adult patients and are consistently found to be associated with schizophrenia and BD.…”
Section: Introductionmentioning
confidence: 54%
“…Abuse and neglect are known to have a negative influence on cognitive functioning in community samples of healthy adults 20,21 and children/adolescents 22,23 as well as in patients with psychosis. 8,24,25 Congruent with other studies, [26][27][28] we have reported that children from densely affected multigenerational families who had a parent affected by schizophrenia or BD had fullscale IQ impairments as well as deficits in specific cognitive domains, such as visual and verbal episodic memory, working memory and executive functions of initiation. 12,16 These domains are among the most impaired in adult patients and are consistently found to be associated with schizophrenia and BD.…”
Section: Introductionmentioning
confidence: 54%
“…Chronicity among schizophrenics was better predicted by ND than any other premorbid characteristics (Ricks & Berry, 1970, cited by McNeil et al, 2003. On the other hand, the development of schizophrenia, schizophrenia-spectrum disorders or schizotypal personality could be predicted using ND (see Hans et al, 1999). Neuromotoric items representing "overflow" (e.g., choreatic movements, tremor) were correlated with mental characteristics, such as language disorders and enuresis; an increase in ND was associated with an increase in rates of mental disorders (McNeil et al, 2003).…”
Section: Psychiatric Disordersmentioning
confidence: 99%
“…On the other hand, the development of schizophrenia, schizophrenia-spectrum disorders or schizotypal personality could be predicted using ND (see Hans et al, 1999). Neuromotoric items representing "overflow" (e.g., choreatic movements, tremor) were correlated with mental characteristics, such as language disorders and enuresis; an increase in ND was associated with an increase in rates of mental disorders (McNeil et al, 2003).…”
Section: Psychiatric Disordersmentioning
confidence: 99%